Study on the mechanical properties and energy dissipation characteristics of concrete subjected to high strain rate and sulfate attack - Liu, Ruixue; Zhang, Lianying; Li, Hailong; Li, Bing (Frontiers in Earth Science, 2023)
Marine structures, such as cross-sea bridges, port constructions, and offshore drilling platforms, are not only subjected to sulfate erosion, but also to various dynamic loads. Analyzing the damage evolution process of concrete under sulfate erosion and impact loads is the key to improving the lifespan of concrete. In order to study the damage evolution process of eroded concrete under high strain rates, the energy dissipation characteristics, basic physics and mechanical properties, and micro-fracture mechanism of sulfate-eroded concrete at different sulfate concentrations (C=0, 3%, 6% and 9%) under high strain rate ranging from 70/s to 85/s are systematically studied by using the split Hopkinson pressure bar (SHPB) test system, X-ray diffractometer and SEM scanning electron microscope. The research results indicate that an increase in sulfate concentration leads to a decrease in Ca(OH)2 content and an increase in Ettringite (AFt) content in concrete specimens; As the sulfate concentration increases, the dynamic peak strength and dynamic elastic modulus of concrete specimens gradually decrease, while the dynamic peak strain of concrete specimens gradually increases; The degree of macroscopic fragmentation in concrete specimens subjected to impact compression becomes increasingly severe with rising sulfate concentrations; As the sulfate concentration increases, the proportion of reflected energy and dissipated energy gradually increases, while that of transmitted energy gradually decreases, and the energy absorption capacity of the sample is significantly improved; The results of the SEM test shows that with the increase of sulfate concentration, a large amount of AFt is generated at the joint fissures and the interface of cement aggregates, the expansion of AFt and the crack development of concrete reduce the integrity and stability of concrete. This study holds significant guidance for the application of concrete in impact situations under a sulfate attack environment.